Waiting times in primary care depending on insurance scheme in Germany - Andres Luque Ramos; Falk Hoffmann; Ove Spreckelsen (BMC Health Services Research, 2018)
Abstract Background Waiting times for an outpatient appointment in Germany differ between insurants of the statutory and private health insurance schemes, especially for specialised care. The aim of this study was to uncover possible differences in waiting times depending on health insurance scheme and to identify predictors for excessive waiting times in primary care. Methods We used data of the Bertelsmann Foundation Healthcare Monitor, which is a repeated cross sectional study dealing with experiences in health care and attitudes towards current health policy themes. We analysed the surveys conducted from 2011 to 2013, with respondents assigned to their health insurance fund, namely AOK, BARMER GEK, BKK, DAK, TK, IKK, other statutory funds and private funds. The mean waiting times for an appointment and spent in a physician’s waiting room, and the satisfaction with waiting times were evaluated with respect to different health insurance funds. A logistic regression model was used to calculate the chance of excessive waiting times with respect to health insurance fund, age, sex, health and socioeconomic status. The ninetieth percentile of the waiting time distribution (10 days) was chosen as the cut-off point between average and excessive. Results A total of 5618 respondents were analysed. Mean waiting times in primary care were low (4.0 days) and homogeneous (SHIs: 3.6–4.9 days), even though privately insured respondents reported shorter waiting times for appointments (3.3 days). They also reported a greater satisfaction with waiting times (77.5%) than SHI insurants (64.5%). However, we identified a group (10.1%), who experienced excessive waiting times in primary care. Compared to privately insured respondents, the chance of excessive waiting times was increased for SHI insurants (highest odds ratio for BKK: 2.17; 95%-CI: 1.38–3.42). Additionally, higher age and residence in East Germany were associated with higher chances of waiting times of 10 days or more. Conclusions Primary care in Germany is readily accessible with generally short waiting times. However, barriers in access to the health care system affect a certain part of patients depending on insurance status, age and region of residence. Ways to improve the access need to be studied.